Discrete cuckoo search applied to capacitated arc routing problem. (2017) - Bensedira, Badis; Layeb, Abdesslam; Habbas, Zineb
Capacitated arc routing problem (CARP) is known as NP-hard combinatorial optimisation problem. Cuckoo search (CS) is a recent meta-heuristic algorithm inspired by breeding the behaviour of cuckoos. CS has proved to be very effective in solving continuous and discrete optimisation problems. In discrete CS for solving CARP (DCSARP), the solution is encoded as a sequence of integer numbers that are positioned according to the order between their components. This discretisation is the key for using CS for solving combinatorial optimisation problems. The experimental results showed that DCSARP can be better than some meta-heuristics in relation to the quality of solution and robustness.